Optimization Design of Mechanical Press Machine Six-link Mechanism based on ADAMS - Chen Xinde (Jixie chuandong)
The mathematical model of optimization design of a mechanical press machine six-link mechanism is built according to the press machine technological requirements,constraint conditions and the optimization objective. By using software ADAMS / View,the optimization design model of the six-link mechanism is constructed,and the optimization design is completed. The result of the optimization design and the slider stroke curves and velocity curves show that the quick-return characteristics of the mechanism is improved by the optimization design and the requirement of the press stamping technology is meet.